Powder injection molding of Stellite 6 powder: Sintering, microstructural and mechanical properties - GÜLSOY, HAMİT ÖZKAN (ELSEVIER SCIENCE SA, 2016)
The purpose of this study was to produce Co-based Stellite 6 superalloy components by using the method of Powder Injection Molding (PIM) and to characterize the microstructural and mechanical properties of the produced components. The experimental studies were started through the formation of feedstock by mixing Stellite 6 powder with a multicomponent binder system. Prepared feedstock was formed by utilizing powder injection molding technique. Then the molded samples were subjected to the solvent and thermal debinding processes. Different sintering cycles were applied to the raw components for the purpose of determining the optimum sintering conditions. The densities of the sintered components were determined in accordance with the Archimedes' principle. The microstructural characterization was performed through scanning electron microscope (SEM) analysis, energy dispersive spectrometry (EDS) analyses, and X-ray diffraction (XRD) analysis. Hardness measurement and tensile test were conducted in order to determine the mechanical properties. The results illustrated that the injection molded Stellite 6 components were composed of fine and equiaxed grains, plenty of carbide precipitates exhibiting homogenous distribution throughout the microstructure formed at the grain boundaries and thus the mechanical properties were considerably high. (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Powder injection molding; Stellite 6; Microstructure; Mechanical properties; ALLOY; BEHAVIOR; CAST; PERFORMANCE; SUPERALLOYS; PHASE